2023
DOI: 10.3390/ijms241512439
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Polyunsaturated Fatty Acid Chains in Mouse Kidneys Were Increased within 5 min of a Single High Dose Whole Body Irradiation

Abstract: To understand the ultra-early reaction of normal organ lipids during irradiation, we investigated the response of lipids, including polyunsaturated fatty acid (PUFA) chains, which are particularly susceptible to damage by ROS, in mice’s kidneys, lungs, brains, and livers within 5 min of single high-dose irradiation. In this study, we set up three groups of C56BL/6 male mice and conducted whole-body irradiation with 0 Gy, 10 Gy, and 20 Gy single doses. Kidney, lung, brain, and liver tissues were collected withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…However, our analysis revealed a significant increase in total PUFA-containing PC species in B4K0H cells (Figure S1), indicating that peroxidation was not a major phenomenon in the irradiated cells. These findings resonate with a recent study by Li et al, who observed a notable increase in PUFA chains within kidney PC, PE, and TG species within 5 min of whole-body irradiation with 10 Gy and 20 Gy in mice [29].…”
Section: Changes In Lipids Associated With Cell Membranessupporting
confidence: 92%
“…However, our analysis revealed a significant increase in total PUFA-containing PC species in B4K0H cells (Figure S1), indicating that peroxidation was not a major phenomenon in the irradiated cells. These findings resonate with a recent study by Li et al, who observed a notable increase in PUFA chains within kidney PC, PE, and TG species within 5 min of whole-body irradiation with 10 Gy and 20 Gy in mice [29].…”
Section: Changes In Lipids Associated With Cell Membranessupporting
confidence: 92%
“…LC-MS/MS is useful to compare the changes in serum protein profiles between low-flux and high-flux HD [22]. LC-MS/MS can assess the efficacy of protein removal from dialyzer membranes by analyzing toxic substances [23,24] and unintentionally lost proteins[25]. In this study, by using mass spectrometric analysis, we first showed that the PMMA membrane exhibited significantly higher adsorption of β2-MG, dermcidin, and immunoglobulin λ-1 light chain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased lipid droplets were commonly found in radioresistant cancer cells as a stress response. Their presence was explained by a decrease in lipid peroxidation induced by ionizing radiation and accounts for an improved antioxidant ability due to higher ROS levels [54][55][56]. Data from previous studies have shown that stem spermatogonia were not killed at low-dose irradiation in mice and immediately began repopulating the seminiferous epithelium with different sperm cells [57].…”
Section: Discussionmentioning
confidence: 99%